Motivações para adoção: uma perspectiva da Psicologia Evolucionista - Rangel, Bianca Tavares (2007)
Parental investment increases the offspring s survival, though it decreases the opportunities for the parents to invest in a future progeny. In a broad sense, this investment is directed to one s own descendant, but in some cases, such as in adoption, resources are directed to non-relatives even in the absence of fitness benefits. Once there are many factors involved in adoption, this study investigated adopters candidates, aiming to analyze aspects considered by them for adopting, based on the Evolutionary Psychology s perspective. We analyzed the judicial proceedings´ files people who had been inlisted for adoption at the 2ª Childhood and Adolescence Law Court, Natal-RN. The adopter s motivations were classified into biological or social reasons. A relationship between adopters´ age and kind of motivation was found: requirements of young people were related to biological reasons while requirements of the old ones were related to social reasons. Fertility, mainly female requirer´s fertility, underlie this relationship, considering that women fertility is strongly influenced by age. The reasons to adopt were also related to the age of the desired child, once that people who wanted children older than 25 months alleged social reasons while those that wanted younger babies alleged biological reasons. There are lots of motives to adopt a child, but the phenomenon of adoption is broadly acknowledged by society as an act of love and the adoptive parents are often regarded as kind and generous people. It was observed, instead, that the reasons to adopt comes from the adopters themselves, related to the fulfillment of personal needs, such as increasing the family, carrying out mother/father role or having a company or someone to care form them in elderly age